Economic-financial analysis for insurance and reinsurance company - NEGRU, Titel (Annals of Spiru Haret University. Economic Series, 2010)
An insurance company has a value as well as its contracts. The efficiency of a company or of a Profit Centre is measurable and the profitability of an insurance product may be quantified. It is possible to assess both company and its products, and take appropriate decisions by using precise criteria. There are methods that satisfy this classic need of evaluation. For the first part of this paper, we will examine the methods like Profit Testing, Embedded Value, Value Added and Total Rate of Return in the context of an endowment insurance product. Then, along with the same example, we will present a critical approach of these methods. We will see that these methods are not always easy to understand and that sometimes the Value Added and the Total Rate of Return are not able to directly show the profitability. Finally, we will perform a sensitivity analysis in order to determine the most influential parameters. This study includes examples of an endowment, a term insurance and an annuity. Data presedent in this article are hypothetical.